Identification of feline erythrocyte antigen 6 and lack of alloimmunization to feline erythrocyte antigen 4 in cats - Thomas Ternisien; Florian Azoulay; Mohammad Y. Bangash; Marie‐Claude Blais (Journal of Veterinary Internal Medicine)
Abstract Background New feline erythrocyte antigens (FEAs) have been described based on the presence of naturally occurring alloantibodies (NOAb), but their immunogenicity and clinical relevance are poorly understood. Hypothesis/Objectives Describe the immunogenicity of FEA 4 after sensitizing FEA 4–negative cats lacking NOAb and characterize anti–FEA 4 alloantibodies produced, including their rate of appearance, agglutination titer, and immunoglobulin class. Animals Nineteen healthy type A cats were blood typed for FEAs 1 to 5 to identify suitable donor‐recipient pairs for FEA 4 sensitization. Methods Four FEA 4–negative cats were transfused with FEA 4–positive red blood cells. Using a gel column technique, posttransfusion samples were screened daily for a week, weekly for a month, and monthly thereafter for anti–FEA 4 alloantibodies. Results Alloantibodies were not detected in the first 3 recipients despite repeated transfusions (1 and 3 additional transfusions for 2 and 1 recipients, respectively). In the 4th recipient, alloantibodies against its donor red blood cells were detected 21 days postsensitization. However, they were not directed against FEA 4, but rather against a novel FEA not yet described. The alloantibodies, named anti–FEA 6, remained detectable for >4 months after sensitization and were determined to be mostly immunoglobulin M based on sulfhydryl treatment. Conclusions and Clinical Importance Feline erythrocyte antigen 4 does not appear to be immunogenic because repeated sensitization of 4 cats failed to produce detectable anti–FEA 4 alloantibodies. A new immunogenic antigen, named FEA 6, has been discovered, but additional studies are needed to document its clinical importance.